1981
DOI: 10.1111/j.1476-5381.1981.tb10482.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation by Clonidine of Purine Release Induced by High Kc1 From the Rabbit Pulmonary Artery

Abstract: The effect of clonidine on the 3H‐purine release evoked by KC1 or (−)‐adrenaline was assessed in the superfused helical strip of the rabbit pulmonary artery pretreated with [3H]‐adenosine. Clonidine (3 × 10−5 M to 10−4 m) significantly enhanced the 3H‐purine efflux evoked by 50 mM KC1 but not by 3 × 10−6M (−)‐adrenaline. This facilitatory effect of clonidine on the KCl‐induced purine release was unaltered by phentolamine 3 × 10−6M. It was absent in arterial segments denervated with 6‐hydroxydopamine 30 jig/ml.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A number of studies on different blood vessels have demonstrated, both mechanically and electrically, neurogenic responses that are not antagonized by oxadrenoceptor antagonists (see . It has been suggested that purines might play a role as cotransmitters with noradrenaline in some vessels (Su, 1975;Head et al, 1977;Katsuragi & Su, 1981;Muramatsu et al, 1981;Sedaa et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on different blood vessels have demonstrated, both mechanically and electrically, neurogenic responses that are not antagonized by oxadrenoceptor antagonists (see . It has been suggested that purines might play a role as cotransmitters with noradrenaline in some vessels (Su, 1975;Head et al, 1977;Katsuragi & Su, 1981;Muramatsu et al, 1981;Sedaa et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Clonidine (3 x mol/l) elicited a sustained contraction of the rabbit pulmonary artery as briefly reported by Katsuragi & Su (1981). Clonidine also reversed the contractile response to adrenaline (3 x mol/l) in the superfused vascular segment and adrenaline thereafter caused a relaxation which was abolished by pretreatment with a 0-adrenoceptor blocker, propranolol.…”
Section: Discussionmentioning
confidence: 62%
“…However, clonidine is also capable of inducing a contractile response in a variety of tissues, particularly vascular smooth muscle (Katsuragi & Su, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many workers have suggested that ATP is a co-transmitter with NA in sympathetic nerves supplying blood vessels (Su, 1975;Head et al, 1977;Katsuragi & Su, 1981;Muramatsu et al, 1981;Sedaa et al, 1986;Burnstock, 1988). Sympathetic nerve stimulation has been shown to produce contraction mediated by both NA and ATP in the rat tail artery (Sneddon & Burnstock, 1984;Vidal et al, 1986), the mesenteric artery (Ishikawa, 1985;von Kugelgen & Starke, 1985;Muramatsu, 1986), the rabbit ear artery (Kennedy et al, 1986), the rabbit saphenous artery (Burnstock & Warland, 1987) and the dog basilar artery (Muramatsu & Kigoshi, 1987).…”
Section: Basal Tone Preparationsmentioning
confidence: 99%